2016
DOI: 10.4172/2471-9846.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Determinants of Antimalarial Drug Use Behaviours: A Systematic Review

Abstract: Introduction: Malaria has been a major global health issue for centuries. Presently, the Artemisinin-based combination therapy (ACTs) is the most effective antimalarial drug and the recommended first line treatment by the WHO for uncomplicated malaria cases. Despite the current global reduction in malaria mortality and morbidity, the burden of malaria is still very significant, especially considering the economic, social, political and public health effects to endemic countries. A major threat to sustaining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(142 reference statements)
2
4
1
Order By: Relevance
“…They highlighted a lack of diagnosis before treatment administration and prescription of inappropriate treatment/combination as well as the lack in the control of practice, particularly in private sector. The study results are consistent with several studies that have reported sub-optimal health worker compliance with ‘test and treat’ malaria guidelines in endemic sub-Saharan African countries including Burkina Faso [ 26 , 59 63 ]. Malaria treatment is still largely presumptive despite the recognition of the usefulness of diagnostics tests and their increasing availability, particularly in public health sectors [ 58 – 61 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They highlighted a lack of diagnosis before treatment administration and prescription of inappropriate treatment/combination as well as the lack in the control of practice, particularly in private sector. The study results are consistent with several studies that have reported sub-optimal health worker compliance with ‘test and treat’ malaria guidelines in endemic sub-Saharan African countries including Burkina Faso [ 26 , 59 63 ]. Malaria treatment is still largely presumptive despite the recognition of the usefulness of diagnostics tests and their increasing availability, particularly in public health sectors [ 58 – 61 ].…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the timeline of previous reports (2006–08), the existence of counterfeit ACT in neighbouring countries [ 30 ] and the high rate of access of this market by the population [ 40 , 41 ] compels us to conclude that there is a strong probability that ACT of poor quality are available in the streets of the country. Financial and geographical accessibility as well as the possibility of unit purchase and price negotiation are the main explanatory reasons for the recourse to street drugs according to our study and this is confirmed by other studies in the African context [ 26 , 40 , 42 , 57 ]. Increased and—above all—continuous repression of supply and sales circuits (including markets, street vendors) would certainly reduce availability of street drugs.…”
Section: Discussionsupporting
confidence: 89%
“…Of those febrile children who received artemisininbased combination, less than half completed the recommended 3-day course of treatment (47.6%). However, no significant association between knowledge of ACT, malaria, or prevention practices and adherence was found, despite suggestions that patient knowledge, attitudes, and beliefs may be strong predictors of adherence [15,31,[37][38][39][40]. Although Bruxvoort et al reported that age, higher household income, higher education level, malaria knowledge, and treatment-seeking behavior are factors facilitating anti-malarial adherence [41], none of the a priori socioeconomic or demographic factors were associated with adherence in this study.…”
Section: Discussioncontrasting
confidence: 78%
“…In contrast, not adhering to this drug leads to poor clinical outcomes, increased morbidity and mortality, and unnecessary healthcare expenditure. Eventually, it might lead to the emergence and spread of drug resistant PF malaria strains [3,7,8]. Patients with uncomplicated PF malaria have strongly discontinued the full or partial course of AL when they were symptom-free since its symptoms improve rapidly after the treatment was initiated [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%